Tasty Catering part b : facing the COVID-19 challenge - Thompson, Kenneth R., (SAGE business cases., 2024)
Tasty Catering started as a hot dog stand in 1984 and by 2020 had blossomed into a catering company with over 10,000 catering events with 200 employees. This did not happen by chance but by analyzing and understanding the market and having the skills, persistence, and careful management to doggedly pursue the dream and meet changing customer requirements. The first Tasty case reviews the history of the organization over 25 years as it grew from a simple hot dog stand into a several million-dollar award-winning business. This expansion as a caterer grew from the realization of the three founders of the importance of uncompromising customer service, product quality, and making employees a key part of the decision process. Tasty Catering Part B begins as the COVID-19 pandemic makes its rapid advance on the Midwest part of the United States and particularly on the market area (Chicago and surrounding areas) served by Tasty Catering. The case focuses on the effect of the pandemic on Tasty Catering’s business and how Tasty had to radically adjust its business model to adjust to the rapid drop in sales while trying to maintain its goals and values toward its customers and its employees. It is a story of working with employees and having a business structure that allows for cash reserves and borrowing power to sustain the business in times of difficulty.